The influence of gender and ethnicity on young adults’ participation in financial education programme - Sabri, Mohamad Fazli; Wijekoon, Rusitha (Canadian Center of Science and Education, 2019)
A major problem encountered by educationalists, community leaders and policy makers is to transfer financial literacy and consumer education successfully to their community. Delivering of ﬁnancial education for youth of a country is one possible intervention to improve the ﬁnancial capabilities of a population. Therefore, for an effective training we have to identify their financial needs. Further they need guidance and access for financial knowledge and money management tools. Therefore, the objectives of this study are to identify the training needs of youth by gender and ethnicity about money management and to determine their interest towards it. The sample was comprised of 220 secondary school students from five schools in Greater Klang Valley/Kuala Lumpur with 112 females and 108 males and the data collection was done using self-administered questionnaire. The results shown that about one third of female youths have preferred to participate on financial literacy programs than male youths (21.5%). In addition, most of the Malay respondents said that they need more information to take efficient decisions on saving, borrowing and insurance, followed by Indians (64%) and Chinese (61.5%). The findings of this study would be used to the development of financial empowerment program of youth in Malaysia in order to enhance their financial literacy.